PENGGUNAAN METODE LATIHAN SIAP UPAYA MENINGKATKAN KEMAMPUAN MENYELESAIKAN PECAHAN DENGAN SISWA KELAS IVA SD NEGERI 010 TEMBILAHAN HULU KECAMATAN TEMBILAHAN HULU - Faridah Faridah (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The problem of the classroom research is low mathematics learning outcome of students class IV A SD Negri 010 Tembilahan Hulu. The learning problem is solved by applying SIAP method with the formulation of the probem: Is the application SIAP method can improve outcomes of mathematics learning ot students class IV A SD Negri 010 Tembilahan Hulu. The research aimed to improve outcomes of mathematics learning on student class IV A SD Negri 010 Tembilahan Hulu by applying SIAP method. The research is expected to be useful for the writer, students, school and government. Based on the result orf the research, by applying SIAP method of learning outcomes of students class IV A SD Negri 010 Tembilahan Hulu incrased significantly. At first, the learning outcomes average 33,20 or not good; in cycle I to 60,40 (good) and cycle II is 78,80 (good). Mastery learning individually and classically increase; at first only 4 or 16.00% of student that mastered the learning; in cycle I to 5 students or 60%; in cycle II to 25 students or 100%. In cycle II, learning has been considered succesful because the student achieves KKM (70) above 85%. The students who have not yet completed will done in remedial learning. The observation result, the student, the student class IV A SD negri 010 Tembilahan Hulu seemed to understand with SIAP method and they could diligent and persistent in learning by this method. Based the result of the research, SIAP method learning has been succesful in fixing the problem of low student outcome class IV A SD Negri 010 Tembilahan Hulu school year 2016/2017